Development of GABUT Media Using Critical Thinking Ability Indicators of High School Students in Learning Mathematical Composition Functions - Vedianty, Adinda Syalsabilla Aidha; Lestari, Andika Setyo Budi; Rayungsari, Maya; Darmayanti, Rani (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to address the lack of interactive learning media specifically designed to enhance students' critical mathematical thinking skills in the topic of function composition. Based on previous research highlighting the potential of viral media in mathematics learning, this study develops and tests an innovative learning medium called GABUT. This medium integrates game elements and interactive learning using QR codes and various levels of problem difficulty. The methodology employed is Research and Development (R&D) with the 4D development model: Define, Design, Develop, and Disseminate. In the Define stage, needs analysis was conducted through interviews and questionnaires. The Design stage involved the initial prototype design of the GABUT media. During the Develop stage, the prototype was tested and evaluated through pre-tests, post-tests, and statistical t-test analysis. The Disseminate stage involved implementing the media in several schools over 12 weeks. The results indicate that GABUT media effectively enhances students' critical mathematical thinking skills, with an average test score improvement of 25% (standard deviation = 5.6, p-value < 0.05). Additionally, 85% of students reported feeling more motivated and engaged in learning mathematics after using this media. Challenges encountered included students' initial adaptation to the new media and issues with "zonk" questions. Improvements were made through initial orientation sessions and revisions to the "zonk" questions. This study makes a significant contribution to mathematics education by providing an innovative and effective learning medium that not only improves students' conceptual understanding of mathematics but also motivates them and increases their participation in the learning process.